PELESTARIAN BUDAYA BALI DALAM ARSITEKTUR TAPAK DAN RESTORAN ARUNA RESORT TEJAPRANA TEGALALANG UBUD – BALI - Suryono, Alwin (Jurnal Arsitektur ARCADE, 2021)
Abstract: Revealing the conservation of Balinese culture forms in the architecture of Site and Aruna Restaurant of Tejaprana resort uses architectural phenomenological approach. The Balinese Culture’s physical-social system is expressed through sensory presence, conceptual systems through goal awareness, and the philosophy through essence awareness. The setting extends from the North-South direction, the Aruna restaurant surrounded by garden in the middle of the site and a temple in the North, preserving the principles of the Balinese Traditional Village setting. The essence of the site order is harmony with the local natural philosophy. Social activities surrounded by gardens in the middle of the site and temple in North form a harmonious-balanced human-nature-God relationship philosophy. The openness of Aruna restaurant is similar to Wantilan's architecture, but with different shape. The pool at the center of the floor and the eight columns around it symbolizes the "natural balance" of the Nawa Sanga concept. The essence of Aruna restaurant is local natural harmony philosophy and spiritual relations, forming a harmonious-balanced human-nature-God relationship philosophy. The principles of traditional village arrangements, Balinese cultural social system, concept of natural balance, bale Wantilan principle, Nawa Sanga concept, Tri Hita Karana philosophy are preserved in the site and Aruna restaurant.).Abstrak: Pengungkapan wujud-wujud Budaya Bali dalam arsitektur Tatanan Tapak dan Restoran Aruna resort Tejaprana dan pelestariannya menggunakan pendekatan fenomenologis arsitektur. Sistem fisik-sosial Budaya Bali diungkap melalui kehadiran inderawi, sistem konsep melalui kesadaran tujuan, dan filosofi melalui kesadaran esensi. Tatanan tapak memanjang arah Utara-Selatan, restoran Aruna dikelilingi taman di tengah tapak dan Pura di Utaranya, melestarikan prinsip tatanan tapak Desa Tradisional Bali, berikut sistem sosial Budaya Bali. Tatanan tapak membentuk Keseimbangan Alam konsep Catur Lokapala. Esensi tatanan tapak adalah keharmonisan-keselarasan dengan alam setempat filosofi Manik Ring Cucupu. Aktivitas sosial dikelilingi taman di tengah tapak dan ibadah di Utaranya membentuk relasi harmonis-seimbang manusia-alam-Tuhan filosofi Tri Hita Karana. Restoran Aruna bersosok terbuka, atapnya bersusun mirip arsitektur Wantilan, namun bentuknya kerucut berlantai dua. Kolam di pusat lantai dan delapan kolom sekelilingnya searah mata angin simbol ‘keseimbangan alam’ konsep Nawa Sanga, memperlihatkan sistem sosial Budaya Bali. Esensi restoran Aruna adalah keharmonisan-keselarasan alam setempat (filosofi Manik Ring Cucupu) dan relasi spiritual, sehingga membentuk relasi harmonis-seimbang manusia-alam-Tuhan (filosofi Tri Hita Karana). Prinsip tatanan desa tradisional, sistem sosial Budaya Bali, konsep keseimbangan alam, prinsip bale Wantilan, konsep Nawa Sanga, filosofi Tri Hita Karana dilestarikan pada tapak dan restoran Aruna.